Pengaruh Perbedaan Konsentrasi Garam terhadap Asam Glutamat Terasi Udang Rebon (Acetes sp.): The Effect of Differences of Salt Concentration on Glutamic Acid of Rebon Shrimp (Acetes sp.) Paste - Rizki Wisnu Murti; Sumardianto Sumardianto; Lukita Purnamayati (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
Rebon shrimp is generally used as raw material for flavoring products, including shrimp paste, paste, and processed into dried rebon. Rebon shrimp has a delicious taste. Simple fermentation produces various products, one of which is shrimp paste. Salt fermentation will cause a savory taste, because the components in rebon shrimp experience a breakdown due to the activity of the protease enzyme. The purpose of this study was to determine the effect of adding different salts to the characteristics of the shrimp paste, and to determine the best salt concentration from the analysis. The research method used a completely randomized design. The treatment in this study was the difference in salt concentration with a concentration of 2, 8, and 14%. The parameters observed were TPC LAB, pH, aw, salt content, glutamic acid, water content and organoleptic. Parametric data were analyzed using ANOVA test and continued with Tukey's HSD test, while non-parametric data were analyzed by Kruskal-Wallis and continued with Mann-Whitney test. The results showed that shrimp paste with 2, 8, and 14% salt concentration had a significant difference (p<5%) on the salt, glutamic acid and water content but did not have a significant difference (p>5%) towards pH and aw. The best shrimp paste formulation in this study with the addition of 2% salt was assessed from glutamic acid 13.68%±0.10 and organoleptic test with a confidence interval of 8.61<μ<8.81.